2021
DOI: 10.1002/cjoc.202100353
|View full text |Cite
|
Sign up to set email alerts
|

Lepithiohydimerins A—D: Four Pairs of Neuroprotective Thiohydantoin Dimers Bearing a Disulfide Bond from Maca (Lepidium meyenii Walp.)

Abstract: Main observation and conclusion An HPLC‐UV‐guided separation was performed and four pairs of unprecedented macathiohydantoin dimers, lepithiohydimerins A—D (1—4) bearing a rare disulfide bond were isolated from the tubers of Maca. Their structures were unambiguously confirmed by NMR spectroscopic, X‐ray crystallographic and electronic circular dichroism (ECD) analyses. At the concentration of 20 μmol/L, compounds 2‐1, 2‐2, and 4‐1 increased the viability of PC12 cells with the cell viability at (72.06 ± 1.14)%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The 1 H NMR spectrum of 1 has peaks indicating an aromatic ring AA′BB′ system [ δ H 7.04 (2H, d, J = 8.4 Hz, H-2′, 6′) and δ H 6.62 (2H, d, J = 8.4 Hz, H-3′, 5′)], one nitrogen-bearing methylene [ δ H 4.72 ( 1 H, d, J = 15.0 Hz, H-7′a) and 4.61( 1 H, d, J = 15.0 Hz, H-1′b)], one saturated methylene [ δ H 2.41 ( 1 H, dd, J = 6.0, 13.2 Hz, H-9a) and 1.95 ( 1 H, dd, J = 7.2, 13.2 Hz, H-9b)], two nonequivalent methines [ δ H 3.85 ( 1 H, dq, J = 6.0, 6.0 Hz, H-7) and 3.83 ( 1 H, ddd, J = 7.2, 6.0, 6.0 Hz, H-8)], and one methyl [ δ H 1.09 (3H, d, J = 6.0 Hz, H 3 -10)]. The 13 C NMR and DEPT spectra display signals corresponding to the above proton-bearing units include two additional quaternary carbonyls assigned as carboxylic ( δ C 172.9, C-4), and thiourea carbonyl ( δ C 182.6, C-2) groups [ 3 , 8 , 9 ], and three quaternary carbon resonances that were assigned as two aromatic carbons, including an oxygen-bearing carbon ( δ C 126.9 and 157.3, respectively) and one nitrogen/oxygen-bearing carbon ( δ C 90.7) ( Table 1 ). These spectroscopic data, and those of the reported thiohydantoin derivatives (Lee et al, 2019; Peng et al, 2021; Yu et al, 2017) indicate that 1 is a thiohydantoin derivative, as confirmed by 2D NMR data analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 1 H NMR spectrum of 1 has peaks indicating an aromatic ring AA′BB′ system [ δ H 7.04 (2H, d, J = 8.4 Hz, H-2′, 6′) and δ H 6.62 (2H, d, J = 8.4 Hz, H-3′, 5′)], one nitrogen-bearing methylene [ δ H 4.72 ( 1 H, d, J = 15.0 Hz, H-7′a) and 4.61( 1 H, d, J = 15.0 Hz, H-1′b)], one saturated methylene [ δ H 2.41 ( 1 H, dd, J = 6.0, 13.2 Hz, H-9a) and 1.95 ( 1 H, dd, J = 7.2, 13.2 Hz, H-9b)], two nonequivalent methines [ δ H 3.85 ( 1 H, dq, J = 6.0, 6.0 Hz, H-7) and 3.83 ( 1 H, ddd, J = 7.2, 6.0, 6.0 Hz, H-8)], and one methyl [ δ H 1.09 (3H, d, J = 6.0 Hz, H 3 -10)]. The 13 C NMR and DEPT spectra display signals corresponding to the above proton-bearing units include two additional quaternary carbonyls assigned as carboxylic ( δ C 172.9, C-4), and thiourea carbonyl ( δ C 182.6, C-2) groups [ 3 , 8 , 9 ], and three quaternary carbon resonances that were assigned as two aromatic carbons, including an oxygen-bearing carbon ( δ C 126.9 and 157.3, respectively) and one nitrogen/oxygen-bearing carbon ( δ C 90.7) ( Table 1 ). These spectroscopic data, and those of the reported thiohydantoin derivatives (Lee et al, 2019; Peng et al, 2021; Yu et al, 2017) indicate that 1 is a thiohydantoin derivative, as confirmed by 2D NMR data analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, no more than 50 naturally occurring thiohydantoin derivatives have been reported in the literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Spiroleiferthione A is a rare 2-thiohydantoin with an unprecedented heterocyclic spiro skeleton that differs from these reported thiohydantoin derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations